Body part terms in conceptualization and language usage - Kraska, Iwona (John Benjamins Publishing Company, 2020)
The volume focuses on body part terms as the vehicle of embodied cognition and conceptualization. It explores the relationship between universal embodiment, language-specific cultural models and linguistic usage practices. The chapters of the volume add to the previous research in a novel way. The presentation of original data from previously undescribed languages spoken by small communities in Africa and South America allows to discover unknown aspects of embodiment and to propose new interpretations. Well-known languages are analyzed from a new perspective relying on the benefits of linguistic corpora. Contrastive and theoretically oriented studies help to pinpoint similarities and differences among languages, as well as tendencies in conceptualization patterns and semantic development of the lexis of body part terms. The volume contributes to the field of linguistics, but also to cognitive science, anthropology and cultural studies.